The flashes collection - Nursi, Said 1873-1960 (From the Risale-i nur collection, 2011)
The Flashes collection comprises thirty-three parts or "Flashes", which expounding the fundamental truths of the Qur'an and belief, and the Practices (Sunna) of the Prophet Muhammad (PBUH), from various angles, set forth important principles for both individual and social life. Also included in this collection are the celebrated treatise on Nature and discussion on Divine Self-Subsistence, which lay open the unsound basis of Naturalist and Materialist philosophies, and demonstrate in reasoned and logical manner the necessity of Divine existence and unity. Other sections answer criticisms made by atheists of certain Qur'anic verses and Hadiths. A Further fruit of this Qur'anic way opened up by the Risalei-i Nur is the solving of important 'mysteries' and 'riddles' of existence, before which, despite all their advances, science, philosophy, and pure reason have remained impotent: namely life and the constant activity in the universe, the true nature and purposes of which are discussed in the Thirtieth Flash. In thus solving the purposes of the existence of man and this world, this work demonstrates man's true happiness and progress to lie in the way of Qur'an and the way of God's Messenger, Peace and blessing be upon him.